The BACE‐1 inhibitor CNP520 for prevention trials in Alzheimer's disease - Ulf Neumann; Mike Ufer; Laura H Jacobson; Marie‐Laure Rouzade‐Dominguez; Gunilla Huledal; Carine Kolly; Rainer M Lüönd; Rainer Machauer; Siem J Veenstra; Konstanze Hurth; Heinrich Rueeger; Marina Tintelnot‐Blomley; et al. (EMBO Molecular Medicine)
Abstract The beta‐site amyloid precursor protein cleaving enzyme‐1 (BACE‐1) initiates the generation of amyloid‐β (Aβ), and the amyloid cascade leading to amyloid plaque deposition, neurodegeneration, and dementia in Alzheimer's disease (AD). Clinical failures of anti‐Aβ therapies in dementia stages suggest that treatment has to start in the early, asymptomatic disease states. The BACE‐1 inhibitor CNP520 has a selectivity, pharmacodynamics, and distribution profile suitable for AD prevention studies. CNP520 reduced brain and cerebrospinal fluid (CSF) Aβ in rats and dogs, and Aβ plaque deposition in APP‐transgenic mice. Animal toxicology studies of CNP520 demonstrated sufficient safety margins, with no signs of hair depigmentation, retina degeneration, liver toxicity, or cardiovascular effects. In healthy adults ≥ 60 years old, treatment with CNP520 was safe and well tolerated and resulted in robust and dose‐dependent Aβ reduction in the cerebrospinal fluid. Thus, long‐term, pivotal studies with CNP520 have been initiated in the Generation Program.